209 Whole Exome Sequencing Identifies Genetic Cause of Histiocytoid Cardiomyopathy. (3rd June 2016) - Rea, Gillian; Homfray, Tessa; Till, Jan; Roses-Noguer, Ferran; Buchan, Rachel J; Wilkinson, Sam; Walsh, Roddy; McKee, Shane; Stewart, Fiona J; Murday, Victoria; Taylor, Robert W; John Baksi, A; et al.
Abstract : Histiocytoid cardiomyopathy (CM) is a rare, distinctive form of cardiomyopathy, characterised by malignant arrhythmias and associated sudden death. 90% of cases present in females <2 years of age. We undertook whole exome sequencing (WES) in five unrelated affected females, including one with parental samples available. In the family trio we identified a de novo nonsense mutation in NDUFB11 (c.262C>T; p. Arg88*), located on the X chromosome and encoding a component of the mitochondrial respiratory chain (MRC). Mutations in NDUFB11, including one identical to the one we describe here, have been reported to cause microphthalmia and linear skin defects syndrome (MLS). During the course of our studies, additional mutations in NDUFB11 were associated with Histiocytoid CM by another group. Four of the affected individuals in our study did not carry variants in NDUFB11. Heterozygous mutations in HCCS (which encodes an important mitochondrially-targeted protein) and COX7B ( which, like NDUFB11, encodes a protein of the MRC) have also previously been identified in MLS syndrome including a case with features of both MLS syndrome and Histiocytoid CM. However, a systematic review of WES data from previously published cases, alongside the four additional cases presented here, did not identify any further mutations in these genes in Histiocytoid CM. We conclude thattruncating variants in NDUFB11 link the distinct phenotypes of Histiocytoid CM and MLS syndrome. Screening for malignant arrhythmias and cardiomyopathy would be appropriate in individuals with MLS syndrome. Additional nuclear encoded mitochondrial or mitochondrial DNA genes are good candidates for further causes of both Histiocytoid CM and MLS syndrome.